Pengembangan Media E-Book Berbasis Aplikasi Office Sway pada Bahan Ajar Modul Bahasa Indonesia Kelas X SMA - Sari, Indah; Sukri Syamsuri, Andi; Nasir (Jurnal Pendidikan dan Pembelajaran, 2022)
This study aims to describe the use, design and results of office sway-based media development in class X Indonesian teaching materials that are valid and practical. This type of research is Research and Development. Media research and development procedures use the Borg & Gall development model, namely: surveys and data collection, planning, development of product drafts, expert validation tests, design revisions and product trials. This research was conducted at SMA Muhammadiyah 1 Unismuh Makassar with Class X research objects totaling 24 students and 1 Indonesian teacher. Research data collection techniques were obtained through observation, interviews, product validation to experts, student and teacher response questionnaires, as well as post-test and pre-test scores. The results of the data were analyzed quantitatively and qualitatively. The results of the study show that the developed media is classified as feasible, as can be seen from the validation of material experts with an average percentage of 78.33% and the validation of media experts with an average percentage of 86%. The Indonesian teacher's response stated that the media was good with an average percentage of 82.10% and the student response questionnaire met practical criteria, the completeness score of student learning outcomes was more than 7.5%, which was 8.45%. Based on this, comparison and analysis can be interpreted that the learning product developed in the form of an E-book based on the Office Sway application in the teaching materials of this module can be declared valid and practical to use as an Indonesian language learning medium.